2013
DOI: 10.1097/01.asw.0000427922.12498.c4
|View full text |Cite
|
Sign up to set email alerts
|

The Safety and Efficacy of Topical Retapamulin Ointment Versus Placebo Ointment in the Treatment of Secondarily Infected Traumatic Lesions

Abstract: Clinical success rates were higher with retapamulin versus placebo in the treatment of patients with secondarily infected traumatic lesions, but the difference between treatment groups was not significant. Retapamulin was well tolerated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…The final selection of publications included 4 placebo-controlled uSSTI trials (35)(36)(37)(38), 12 linezolid trials (39-50), 3 ceftaroline trials (51-53), 1 retrospective ceftaroline secondary analysis (54), and 2 nonantibacterial treatment trials of UV light for erysipelas (23,24) (Fig. 1).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The final selection of publications included 4 placebo-controlled uSSTI trials (35)(36)(37)(38), 12 linezolid trials (39-50), 3 ceftaroline trials (51-53), 1 retrospective ceftaroline secondary analysis (54), and 2 nonantibacterial treatment trials of UV light for erysipelas (23,24) (Fig. 1).…”
Section: Methodsmentioning
confidence: 99%
“…The four trials as proxy for placebo included 234 subjects with a range of uncomplicated infections reported as impetigo, folliculitis, SITL, and pyoderma (Table 1). Publication dates were from 1974 to 2013, three of the trials enrolled a subset of subjects Ͻ18 years of age, and one publication required certified translation from French to English (35)(36)(37)(38). Each trial reported a TOC clinical treatment response; none reported an early clinical treatment response.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…This was presumably because clinical success rates were quite high in the placebo arm (see Table). 4…”
Section: Infected Woundsmentioning
confidence: 99%